THE IMPORTANCE OF LEAN MANAGEMENT PRINCIPLES FOR MAINTENANCE IN IRAQI REFINERIES - Mokhef Al Kitab M.A.A.H.; Thiruchelvam S.A.; Gaaz T.S. (Taylor's University, 2024)
Maintenance in Iraqi oil and gas (O&G) firms is critical in providing customers with operations, maintenance, and services for O&G products. In recent decades, fresh theories for enhancing the performance of the oil and gas business, such as lean management and six sigma, have emerged. The lean management concept is used in this study to improve services and maintenance in the Iraqi O&G industry. A quantitative technique was used to reach the study's aim, including a questionnaire that was produced and sent electronically. The assessment was undertaken at the Najaf refinery in southern Iraq and the A-Dora refinery in the centre of Iraq. It was discovered that finding value in lean management plays no significant effect on maintenance performance in the Iraqi O&G industry. Furthermore, it was discovered that the map value stream greatly influences maintenance performance and that establishing flow in lean management has no substantial impact on maintenance performance in the O&G business. Furthermore, the data showed that establishing pull has no substantial impact on the O&G industry's maintenance performance and that chasing perfection has no significant impact on maintenance performance. The researcher made several recommendations and future work proposals to increase O&G maintenance performance. 2023 Taylor's University. All rights reserved.